To convert the equation from standard form \( Ax + By = C \) to slope-intercept form \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept, you can follow these steps.
Given the equation: \[ 4x - y = 1 \]
-
Start by isolating \( y \). You can do this by moving \( 4x \) to the right side of the equation: \[ -y = -4x + 1 \]
-
Next, multiply through by -1 to solve for \( y \): \[ y = 4x - 1 \]
Now the equation is in slope-intercept form \( y = mx + b \), where \( m = 4 \) and \( b = -1 \).
Thus, the slope-intercept form of the equation \( 4x - y = 1 \) is: \[ y = 4x - 1 \]